Soldering Materials (IntechOpen, 2023)
This book is about solders and their composition and focuses on material characterizations and the methods used to make alloys and determine their structures, physical properties and applications. Physical properties and the factors that control them and theoretical verification are the main contents of this book. Corrosion of solders is included in the coverage of the properties related to solder composition and mechanical properties.